Grassy starch - Jutta, Mariam; Zawawi, Abu Hanafiah (University Putra Malaysia, 2012)
The edible portion of grains or cereals are staple foods consumed throughout the world and through human history. Today they provide more food in quantity and quality than any other plants. These grains, that include rice (Oryza sativa), wheat (Triticum spp.), maize (Zea mays), oats (Avena sativa), barley (Hordeum vulgare) and many other lesser known species, are nothing but the fruits of grasses.